Resiliensi Masyarakat Terhadap Bencana Banjir - Sri Jayanti Rasyid; Firdaus W. Suhaeb (Rayhan Intermedia, 2023)
This research was conducted to determine and describe community resilience to flood disasters in Suli Village, Suli District, Luwu Regency. This type of research is qualitative research with a descriptive approach by determining research subjects through purposive sampling techniques. Data collection techniques use observation, interviews and documentation. The analysis technique uses data reduction, data presentation and drawing conclusions. The results of this research show that community resilience to flood disasters is 1) The ability to manage risk, 2) The community's ability to adapt before a flood occurs, during a flood and after a flood occurs, and 3) The community's ability to meet food needs.